An outline for a series of twelve demonstration lectures - Berry, Ethel Esther (My University, 1907)
Introduction: It is a fact that Domestic Science is regarded with more esteem at present than it ever has been in the past. It has won its place of honor among the sciences upon its own merits. People are beginning to see its importance in the homes and in the schools, feel the dignity of those in the work and realize the future of such a practical study. With the great growth of Domestic Science there comes a demand from Chautauquas all over the United States for Domestic Science Departments. In this thesis such lessons have been selected as would be suitable for a Chautauqua course or any short course in the subject. The time allowed at such occasions varies from thirty minutes to one hour, consequently such articles must be chosen as can be conveniently prepared.
Citation: Berry, Ethel Esther. An outline for a series of twelve demonstration lectures. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Domestic Science; Education; Value of Domestic Science; Theses; Manuscripts (documents)